2015
DOI: 10.7860/jcdr/2015/12602.5929
|View full text |Cite
|
Sign up to set email alerts
|

Does Hollowing of Complete Denture Enhance Retention? – A Pilot Study

Abstract: The denture retention and stability, chewing and comfort values of conventional dentures and hollow dentures were slightly better for conventional dentures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Our study resembling Sheridan et al's report showed that the peak formaldehyde release, which was one of the most important factors of cytotoxicity, was observed during the first 24 hours and subsided over time. Except for Tsuchiya et al [21], who determined formaldehyde release similar to the present study, other researchers have evaluated just free methyl methacrylate monomer [19,22,24,27]. However, formaldehyde is more cytotoxic than methyl methacrylate, even at lower concentrations [21].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our study resembling Sheridan et al's report showed that the peak formaldehyde release, which was one of the most important factors of cytotoxicity, was observed during the first 24 hours and subsided over time. Except for Tsuchiya et al [21], who determined formaldehyde release similar to the present study, other researchers have evaluated just free methyl methacrylate monomer [19,22,24,27]. However, formaldehyde is more cytotoxic than methyl methacrylate, even at lower concentrations [21].…”
Section: Discussionsupporting
confidence: 51%
“…MMA molecules can be associated with saliva's proteins making large molecules responsible for oral tissue allergic reactions [17,18]. Cheilitis, stomatitis, burning mouth, and painful sensation are some side effects of resin acrylic materials reported in people who have received a complete or partial denture [19]. All cells in the human body contain some amount of formaldehyde, which is produced due to the metabolism of serine, glycine, methionine, and other amino acids in the human body [4].…”
Section: Introductionmentioning
confidence: 99%